The influence of age and captivity on cardiac structure and function in rhesus macaques - T. G. Dawkins; B. A. Curry; A. Drane; V. N. Rivas; Y. Ueda; J. A. Stern; D. Philips; J. Negron-Del Valle; Lauren Brent; James Higham; Angelina Ruiz-Lambides; Noah Snyder-Mackler; et al. (GeroScience, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Perlecan Domain-V Enhances Neurogenic Brain Repair After Stroke in Mice - Amanda L. Trout; Michael P. Kahle; Jill M. Roberts; Aileen Marcelo; Leon de Hoog; Jeffery A. Boychuk; Stephen L. Grupke; Antonio Berretta; Emma K. Gowing; Carie R. Boychuk; Amanda A. Gorman; Danielle N. Edwards; et al. (Translational Stroke Research, 2021)
The extracellular matrix fragment perlecan domain V is neuroprotective and functionally restorative following experimental stroke. As neurogenesis is an important component of chronic post-stroke repair, and previous studies have implicated perlecan in developmental neurogenesis, we hypothesized that domain V could have a broad therapeutic window by enhancing neurogenesis after stroke. We demonstrated that domain V is chronically increased in the brains of human stroke patients, suggesting that it is present during post-stroke neurogenic periods. Furthermore, perlecan deficient mice had significantly less neuroblast precursor cells after experimental stroke. Seven-day delayed domain V administration enhanced neurogenesis and restored peri-infarct excitatory synaptic drive to neocortical layer 2/3 pyramidal neurons after experimental stroke. Domain V’s effects were inhibited by blockade of α2β1 integrin, suggesting the importance of α2β1 integrin to neurogenesis and domain V neurogenic effects. Our results demonstrate that perlecan plays a previously unrecognized role in post-stroke neurogenesis and that delayed DV administration after experimental stroke enhances neurogenesis and improves recovery in an α2β1 integrin-mediated fashion. We conclude that domain V is a clinically relevant neuroprotective and neuroreparative novel stroke therapy with a broad therapeutic window.

Correction to: Common findings of blaCTX-M-55-encoding 104–139 kbp plasmids harbored by extended-spectrum β-lactamase-producing Escherichia coli in pork meat, wholesale market workers, and patients with urinary tract infection in Vietnam - T. A. V. Hoang; T. N. H. Nguyen; S. Ueda; Q. P. Le; T. T. N. Tran; T. N. D. Nguyen; T. V. K. Dao; M. T. Tran; T. T. T. Le; T. L. Le; T. Nakayama; I. Hirai; et al. (Current Microbiology, 2019)

Immunohistochemical Cross-Reactivity Between Paracoccidioides sp. from Dolphins and Histoplasma capsulatum - Godai Shumoto; Keiichi Ueda; Sayaka Yamaguchi; Takashi Kaneshima; Toshihiro Konno; Yoshie Terashima; Atsushi Yamamoto; Luciene A. Nagashima; Eiko N. Itano; Ayako Sano (Mycopathologia, 2018)

Common findings of bla CTX-M-55-encoding 104–139 kbp plasmids harbored by extended-spectrum β-lactamase-producing Escherichia coli in pork meat, wholesale market workers, and patients with urinary tract infection in Vietnam - T. A. V. Hoang; T. N. H. Nguyen; S. Ueda; Q. P. Le; T. T. N. Tran; T. N. D. Nguyen; T. V. K. Dao; M. T. Tran; T. T. T. Le; T. L. Le; T. Nakayama; I. Hirai; et al. (Current Microbiology, 2017)

Resightings of branded Steller sea lions at wintering haul-out sites in Hokkaido, Japan 2003â2006 - Takeomi Isono; Vladimir N. Burkanov; Noritaka Ueda; Kaoru Hattori; Orio Yamamura (Marine Mammal Science, 2009)

Molecular biological research on olfactory chemoreception in fishes - H. Hino; N. G. Miles; H. Bandoh; H. Ueda (Journal of Fish Biology, 2009)
This review describes recent molecular biological research on olfactory chemoreception in fishes. The recent rapid development of molecular biological techniques has provided new valuable information on the main and vomeronasal olfactory receptor (OR) genes, the axonal projection from ciliated, microvillous and crypt‐olfactory receptor cells to the olfactory bulb, properties of odorant substances and olfactory imprinting and homing in salmon. Many important questions, however, remain unanswered on functional differences among OR genes, on ligand binding to each OR and on the molecular biological mechanisms underlying olfactory imprinting and homing in salmon. Olfactory chemoreception is believed to be the oldest sensory cue for both animal survival and adaptation to various different environments. Further intensive molecular biological research on olfactory memory formation and remembrance should be carried out to clarify the fundamental process of olfactory chemoreception in fishes.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Relationship between eyed‐egg percentage and levels of cortisol and thyroid hormone in masu salmon Oncorhynchus masou - M. Mingist; T. Kitani; N. Koide; H. Ueda (Journal of Fish Biology, 2007)
A possible cause of the low eyed‐egg percentage that afflicts pond‐reared masu salmon Oncorhynchus masou at a fish hatchery (Kumaishi Fish Hatchery, Hokkaido, Japan) was investigated. Serum cortisol levels of masu salmon during the spawning period were compared between individuals from Kumaishi and those from another station (Mori). Cortisol, thyroxine (T 4 ) and triiodothyronine (T 3 ) hormones were also measured in eyed eggs and their levels were compared to the eyed‐egg percentage. Serum cortisol levels were significantly higher at Kumaishi than at Mori in May and July of the breeding season. At the Kumaishi station, there was a linear positive relationship between serum cortisol and fertilized‐egg cortisol levels of female masu salmon. As cortisol levels in both ovulating females and eyed eggs increased, the eyed‐egg percentage decreased, indicating a highly significant negative relationship between cortisol levels and eyed‐egg percentage. In contrast, as T 3 and T 4 levels in eyed eggs increased, the eyed‐egg percentage increased. The strong positive correlation between high cortisol levels in serum and in eyed eggs at Kumaishi indicates that the frequently higher cortisol levels may have caused the lowering of the eyed‐egg percentage.

Population Research of Genetic Polymorphism at Amino Acid Position 631 in Chicken Mx Protein with Differential Antiviral Activity - T. Seyama; J. H. Ko; M. Ohe; N. Sasaoka; A. Okada; H. Gomi; A. Yoneda; J. Ueda; M. Nishibori; S. Okamoto; Y. Maeda; T. Watanabe (Biochemical Genetics, 2006)

Molecular mechanisms involved in anti-inflammatory effects of proton pump inhibitors - O. Handa; N. Yoshida; N. Fujita; Y. Tanaka; M. Ueda; T. Takagi; S. Kokura; Y. Naito; T. Okanoue; T. Yoshikawa (Inflammation Research, 2006)

Roles of Aquaporin-3 Water Channels in Volume-Regulatory Water Flow in a Human Epithelial Cell Line - H. Kida; T. Miyoshi; K. Manabe; N. Takahashi; T. Konno; S. Ueda; T. Chiba; T. Shimizu; Y. Okada; S. Morishima (The Journal of Membrane Biology, 2005)

Effects of an Environmental Estrogen on Male Gulf Pipefish, Syngnathus scovelli (Evermann and Kendall), a Male Brooding Teleost - N. Ueda; C. Partridge; J. Bolland; J. Hemming; T. Sherman; A. Boettcher (Bulletin of Environmental Contamination and Toxicology, 2005)

A novel antipsychotic, perospirone, has antiserotonergic and antidopaminergic effects in human brain: findings from neuroendocrine challenge tests - M. Iwakawa; T. Terao; A. Soya; H. Kojima; Y. Inoue; N. Ueda; R. Yoshimura; J. Nakamura (Psychopharmacology, 2004)

Comparative analyses of serum vitellogenin levels in male and female Reeves' pond turtles ( Chinemys reevesii ) by an immunological assay - Y. Ueda; H. Hoshi; T. Uemura; Y. Kamata; N. Tada; M. Saka (Journal of Comparative Physiology B, 2004)

Chloroplast DNA phylogeography of Fagus crenata (Fagaceae) in Japan - N. Fujii; N. Tomaru; K. Okuyama; T. Koike; T. Mikami; K. Ueda (Plant Systematics and Evolution, 2002)

Renal damage and salt-dependent hypertension in aged transgenic mice overexpressing endothelin-1 - T. Shindo; H. Kurihara; K. Maemura; Y. Kurihara; O. Ueda; H. Suzuki; T. Kuwaki; K.-H. Ju; Y. Wang; A. Ebihara; H. Nishimatsu; N. Moriyama; et al. (Journal of Molecular Medicine, 2002)

Intramolecular Stable Isotope Ratios of N 2 O in the Tropical Swamp Forest in Thailand - N. Boontanon; S. Ueda; P. Kanatharana; E. Wada (The Science of Nature, 2000)

”In vivo cryotechnique" in combination with replica immunoelectron microscopy for caveolin in smooth muscle cells - I. Takayama; N. Terada; T. Baba; H. Ueda; Y. Kato; Y. Fujii; S. Ohno (Histochemistry and Cell Biology, 1999)

Geographical variations in the trophic structure of the plankton community along a eutrophic–mesotrophic–oligotrophic transect - S. Uye; N. Iwamoto; T. Ueda; H. Tamaki; K. Nakahira (Fisheries Oceanography, 1999)
The geographical variations in trophic structure of the plankton community, as defined by total and relative carbon biomass of phytoplankton (PP), bacteria (BA), heterotrophic nanoflagellates (HNF), microzooplankton (MZ), and herbivorous (HNZ) and carnivorous net‐zooplankton (CNZ), were investigated along an inshore–offshore transect from the innermost part of Osaka Bay to the Pacific Ocean off Kii Channel, Japan, in June 1991. Based on physico‐chemical properties of the water and topographical features, the transect was divided into three trophic areas, i.e. eutrophic, mesotrophic and oligotrophic ones. The average carbon biomass of the total plankton community was highest (438 mg m −3 ) in the inshore eutrophic area, and declined steeply offshore (141 and 26.6 mg m −3 in the mesotrophic and oligotrophic areas, respectively). In the offshore oligotrophic area, the relative biomass of BA to PP and the relative biomass of small heterotrophs (i.e. BA, HNF and MZ) to the total heterotrophs were higher than in the other areas, indicating that the microbial food chain predominated. In the mesotrophic area, the biomass of HNZ (primarily copepods) was conspicuously high, even higher than that of PP, suggesting that the traditional grazing food chain prevailed. Because of this short food chain, a productive fishing ground is formed there. In the eutrophic area, the biomass of HNZ was much smaller relative to the enormous biomass of PP, indicating that a considerable amount of primary production was not utilized directly by the metazoan zooplankton. However, the relative contribution of the small heterotrophs to the total heterotrophs’ biomass was higher in this area, as in the oligotrophic area.

The effects of selenium deficiency on differentiation, degradation, dand cell lysis of L8 rat skeletal muscle cells - Y. Ueda; P. D. Whanger; N. E. Forsberg (Biological Trace Element Research, 1999)

Hydrothermal carbonates in altered wall rocks at the Uwamuki Kuroko deposits, Japan - N. Shikazono; M. Hoshino; M. Utada; M. Nakata; A. Ueda (Mineralium Deposita, 1998)

Rapid detection of African horsesickness virus by the reverse transcriptase polymerase chain reaction (RT-PCR) using the amplimer for segment 3 (VP3 gene) - K. Sakamoto; R. Punyahotra; N. Mizukoshi; S. Ueda; H. Imagawa; T. Sugiura; M. Kamada; A. Fukusho (Archives of Virology, 1994)

Generation and characterization of the human immunodeficiency virus type 1 mutants - A. Adachi; N. Ono; H. Sakai; K. Ogawa; R. Shibata; T. Kiyomasu; H. Masuike; S. Ueda (Archives of Virology, 1991)

Characterization of a temperature-sensitive mutant in the RNA polymerase PB2 subunit gene of influenza A/WSN/33 virus - K. Yamanaka; N. Ogasawara; M. Ueda; H. Yoshikawa; A. Ishihama; K. Nagata (Archives of Virology, 1990)

Cross-reactivity among cowpox, ectromelia and vaccinia viruses with monoclonal antibodies recognizing distinct antigenic determinants in A-type inclusion bodies - N. Kitamoto; S. Tanimoto; K. Hiroi; H. Miyamoto; N. Wakamiya; S. Ueda; S. Kato (Archives of Virology, 1986)

Polypeptide analysis with monoclonal antibodies of A type inclusion bodies induced by cowpox virus - N. Kitamoto; S. Tanimoto; K. Hiroi; T. Tanaka; H. Miyamoto; N. Wakamiya; K. Ikuta; S. Ueda; S. Kato (Archives of Virology, 1986)

Cross-reactivity between cowpox and vaccinia viruses with monoclonal antibodies - N. Kitamoto; E. Goto; S. Tanimoto; T. Tanaka; H. Miyamoto; N. Wakamiya; K. Ikuta; S. Ueda; S. Kato (Archives of Virology, 1984)